The impact of self-medication with antifungal agents on vulvovaginal candidiasis: An integrative literature review (Research, Society and Development, 2025)
Vulvovaginal candidiasis (VVC) is a common infection among women of reproductive age and is often self-treated with antifungal agents purchased without a medical prescription. Although this practice facilitates access to treatment, it can lead to significant health consequences, such as misdiagnosis, inappropriate medication use, and increased fungal resistance. This integrative review aimed to gather scientific evidence on the various impacts of self-medication with antifungals in the context of VVC. A total of eight studies published between 2000 and 2025 were analyzed, selected from the BVS, PubMed, and EuropePMC databases. The findings reveal a high prevalence of infection, especially in recurrent cases, and highlight the frequent use of medications without professional guidance. In addition, greater resistance of non-albicans species to the most commonly used antifungals was observed. Strategies such as professional guidance, the use of vaginal pH tests, and the strengthening of educational actions may contribute to safer and more effective care. Therefore, the importance of public policies that encourage the rational use of these medications and expand access to information and tools supporting accurate diagnosis is reinforced.